2019
DOI: 10.3390/polym11091479
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Free Flame-Retardant Compounds. Thermal Decomposition and Flammability Behavior for Alternative Polyethylene Grades

Abstract: The effect of six halogen-free flame retardant (FR) formulations was investigated on the thermal stability of two low-density polyethylenes (LDPE) and one linear low-density polyethylene (LLDPE), by means of thermogravimetric analysis (TGA) under nitrogen and air atmosphere. The relative data were combined with flammability properties and the overall performance of the FRs was correlated with the type of branching in the polyethylene grades and to their processing behavior. The thermal degradation kinetics was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Al-Salem and Liu et al [13,14] studied pyrolysis kinetics of the high density polyethylene. Luyt [15] investigated the effect of six halogen-free flame retardant (FR) formulations on the thermal stability of two low-density polyethylenes (LDPE) and one linear low-density polyethylene (LLDPE). Park et al [16] characterized the pyrolysis of waste polyethylene using two successive stages with auger and fluidized bed reactors.…”
mentioning
confidence: 99%
“…Al-Salem and Liu et al [13,14] studied pyrolysis kinetics of the high density polyethylene. Luyt [15] investigated the effect of six halogen-free flame retardant (FR) formulations on the thermal stability of two low-density polyethylenes (LDPE) and one linear low-density polyethylene (LLDPE). Park et al [16] characterized the pyrolysis of waste polyethylene using two successive stages with auger and fluidized bed reactors.…”
mentioning
confidence: 99%
“…The SiO 2 layer increased the formation of carbon and slowed down the release of heat. [46,47] Therefore, the combustion performance of LDPE4 and LDPE5 were improved with the addition of SiO 2 @MAPP.…”
Section: Smoke Density Analysismentioning
confidence: 99%
“…PEs are one of the most potential materials of value-adding in case of accurate formulation modifications [18]. It is of great importance to know the grades of PE as their flame performance is correlated with their chemical structure (i.e., branching type) and FR formulations [18]. The structure and properties of PE main grades, including density, crystallinity, LOI, thermal conductivity, melting temperature, and molecular weight are summarized in Table 1.…”
Section: Pe Grades and Propertiesmentioning
confidence: 99%
“…The nitrogen and phosphorus-based flame retardants used as treatments in PE, LDPE, LLDPE, and HDPE are listed in Table 2 with emphasis on the effect each additive have on the polymer matrix. In an interesting study reported by Luyt et al [18], six FR compositions obtained by mixing commercial N-and P-containing FRs were embedded into different grades of LDPE and LLDPE to evaluate their effects on thermal stability and fire-resistance. LDPE grade produced in an autoclave reactor showed the best flame retardancy performance (UL 94 V0, char residue: 10 ± 1% at 800 • C) when 35 wt.% of the triazine (TRZ) derivative and APP formulated FR was incorporated.…”
Section: Nitrogenmentioning
confidence: 99%